Indigenous Textual Cultures : Reading and Writing in the Age of Global Empire - Wanhalla, Angela; Paterson, Lachy, 1958-; Ballantyne, Tony, 1972- (Book collections on Project MUSE., 2020)
"INDIGENOUS TEXTUAL CULTURES assesses how indigenous literacy, texts, and orality were related in a range of colonial situations, across three centuries, and the repercussions of these interactions today. Native writers deployed the written word to assert intellectual power within the uneven terrains of colonial rule. This collection highlights the role of literary practices in preserving indigenous knowledge traditions and in the dynamic, creative remaking of indigenous social life, cultural understanding, and political aspiration under imperialism. The essays also question the supposed hegemony of literacy within modernity by illustrating how it operates alongside orality, rather than replacing it. The volume brings together work on the Pacific, Australasia, North America, and Africa, highlighting a range of text genres that indigenous peoples contributed to or produced, including letters, journals, appeals to government, newspapers, pamphlets, and books. The variety and range of indigenous textual cultures are highlighted in the book's four parts. The first part examines material from Pacific archives that house an abundance of indigenous written material and explores why these repositories are largely under-utilized. Noelani Arista argues that scholars should learn the Hawaiian language in order to use the extensive Hawaiian language textual archive and should be trained to explore texts that had oral beginnings. The second section explores the relationship between orality and textuality in more depth. Keith Thor Carlson compares communication systems and processes used by settler colonists and by Salish people on Canada's Pacific coast, explicating a Salish time-based oral literacy that is inscribed within their landscapes. For missionaries or colonial officials, literacy and print were often seen as tools to govern or transform indigenous subjects, and the third section investigates indigenous peoples' negotiations with these discourses and technologies. Laura Rademaker argues that the Anindilyakwa people in Australia abandoned textual practices that missionaries advocated in the 1940s; instead, the Anindilyakwa wrote love letters, critique, and petitions adapted to their own needs that went against missionary prescriptions. The fourth section highlights the projection of indigenous voices through writing. Ivy Schweitzer considers Samuel Occom, a mid-18th-century Mohegan of New England, who used his writing skills to help fellow Native Americans; Schweitzer argues that literacy in pre-contact Native America differed from, and was much wider in scope than, textual symbolic systems"--